Shedding Light on Electrocatalysts: Practical Considerations for Operando Studies with High‐Energy X‐Rays - Rebecca K. Pittkowski (ChemElectroChem, 2024)
Abstract Operando studies using high‐energy X‐rays from synchrotron sources are essential for unraveling the complex material transformation that electrocatalysts undergo under operating conditions. This article explores key considerations to perform these experiments and the insights gained from such studies on nanostructured electrocatalysts. Critical factors include optimizing electrochemical performance while obtaining high‐quality X‐ray signals, which often require compromises. The electrochemical operando cell design is crucial, and several different cells are discussed here. Working electrode geometries parallel to the X‐ray beam, probed with a microfocused beam, are emerging as promising solutions for realistic electrochemical performance in operando cells. Careful attention must also be paid to the electrochemical measuring conditions, electrode loading, and beam damage to ensure reliable experiments. When carefully performed and by combining multiple characterization techniques, operando studies with high‐energy X‐rays offer the unique possibility to fully understand the structure of the active electrocatalyst.